Thermo-Mechanical Properties of Unsaturated Polyester Reinforced with SiliconCarbide Powder And with Chopped Glass Fiber (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The work studied the effectoffine silicon carbide (SiC) powder with (0,3,5,7)wt % on the thermal conductivity and mechanical properties of unsaturated polyester composite in the presence of a fixed amount of chopped glass fiber. The hand lay-up technique was employed to preparethe required samples. Results showed that tensile, impact strength and thermal conductivity increased with increasing the weight fraction of reinforced materials.